Biomimetic Nanoemulsions for Oxygen Delivery In Vivo. Issue 49 (8th October 2018) - Zhuang, Jia; Ying, Man; Spiekermann, Kevin; Holay, Maya; Zhang, Yue; Chen, Fang; Gong, Hua; Lee, Joo Hee; Gao, Weiwei; Fang, Ronnie H.; Zhang, Liangfang
Abstract: Blood transfusion is oftentimes required for patients suffering from acute trauma or undergoing surgical procedures in order to help maintain the body's oxygen levels. The continued demand worldwide for blood products is expected to put significant strain on available resources and infrastructure. Unfortunately, efforts to develop viable alternatives to human red blood cells for transfusion are generally unsuccessful. Here, a hybrid natural–synthetic nanodelivery platform that combines the biocompatibility of the natural RBC membrane with the oxygen‐carrying ability of perfluorocarbons is reported. The resulting formulation can be stored long‐term and exhibits a high capacity for oxygen delivery, helping to mitigate the effects of hypoxia in vitro. In an animal model of hemorrhagic shock, mice are resuscitated at an efficacy comparable to whole blood infusion. By leveraging the advantageous properties of its constituent parts, this biomimetic oxygen delivery system may have the potential to address a critical need in the clinic. Abstract : A biomimetic oxygen delivery carrier is synthesized by employing a natural cell membrane as a stabilizer for perfluorocarbon nanoemulsions. The resulting formulation exhibits a high capacity for delivering oxygen and can be used to successfully resuscitate mice in an animal model of hemorrhagic shock. This natural–synthetic platform may eventually be used to help alleviate the impact of blood shortages in clinical settings.